Adaptability of Nile Tilapia (Oreochromis niloticus) in Biofloc Systems: Effects on Growth, Feed Efficiency, Water Quality, and Economic Viability - Farhana Islam, Shawon; MD. Najmul, Islam; Islam, Ferdous; MD. Hosne, Azam (Journal of Aquaculture and Fish Health, 2025)
Biofloc Technology (BFT) has emerged as a sustainable and cost-effective solution for aquaculture, addressing critical challenges such as water conservation, feed efficiency, and environmental impact. This study investigates the adaptability of Nile tilapia at different life stages to BFT systems, focusing on growth performance, survival rates, feed conversion ratios (FCR), and economic viability. Three treatments were evaluated: 20-day-old tilapia fry (T1), 35-day-old juvenile tilapia (T2), and 50-day-old adult tilapia (T3), each with three replications. Over a 14-week rearing period, weekly sampling revealed significant differences (p<0.05) in growth and survival rates. Juvenile tilapia (T2) demonstrated superior adaptability, achieving the highest final weight gain (292.33 ± 5.54 g), survival rate (98.67 ± 0.58%), and economic return, with the best benefit-cost ratio (BCR: 1.426) and lowest FCR (0.647 ± 0.028). These findings highlight the potential of BFT to enhance sustainable aquaculture practices by improving feed efficiency, reducing operational costs, and increasing profitability for farmers. This study underscores the commercial viability of using juvenile tilapia in BFT systems, offering a scalable and environmentally friendly approach to meet the growing demand for aquaculture production.